Self-repairing surface layer mortar and preparation method thereof
By introducing a combination of self-healing silicon microspheres and composite expansion agents into the surface layer mortar, a polymer network structure and chemical reaction are formed, which solves the problem of insufficient crack resistance, wear resistance and impact resistance of the surface layer mortar, and realizes the Surface mortar with high mechanical properties and self-healing function.
Patent Information
- Application Number
- CN202411523797.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
AI Technical Summary
The existing surface layer self-leveling mortar has insufficient performance in terms of crack resistance, wear resistance and impact resistance, resulting in problems such as peeling, sanding, lump surface and cracking after use.
It adopts a self-repair surface mortar containing cement, aggregate, filler, redispersible latex powder, self-repair silicon microspheres, polyvinyl alcohol fibers, defoaming agents, dispersing agents, composite expansion agents and water reducing agents. By self-healing the porous structure of silicon microspheres and polymer network structure, combining the chemical reactions of calcium sulfaluminate, calcium oxide and calcium sulfate, the cracks are sealed and self-healed.
It significantly improves the mechanical properties, wear resistance and impact resistance of the surface mortar, has the characteristics of fast early strength and high later strength, and has self-repair function, which can effectively prevent cracks from expanding and repairing.
Smart Images

Figure CN119285306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a self-repairing surface mortar and a preparation method thereof. Background Art
[0002] Self-leveling mortar is a kind of functional building mortar with bearing capacity and decorative function. When using, add water according to the specified water-to-material ratio and mix evenly. After mechanical pumping or manual construction, the high fluidity of the mortar can automatically level to form a flat surface, which can effectively reduce labor costs and improve construction efficiency.
[0003] Self-leveling material is a ground building material made of inorganic or organic cementitious materials as the base material, with aggregates, mineral fillers and chemical admixtures. It is a kind of functional building mortar with load-bearing capacity and decorative function. When used, water is added and stirred according to the prescribed proportion, or the powder and liquid are mixed evenly. After mechanical pumping or manual construction, there is no need for manual spreading and vibration. The high fluidity of the slurry automatically levels to form a flat surface.
[0004] According to the difference in load-bearing requirements, self-leveling mortar can be divided into surface self-leveling materials and cushion self-leveling mortar, and the two are generally used in combination. The surface self-leveling mortar is different from the cushion self-leveling mortar. The cushion self-leveling mortar is usually used as a leveling layer, and then the surface materials such as floor tiles, floors, carpets, etc. are laid on it. It is not in direct contact with the air and is not prone to cracking due to drying shrinkage. The surface self-leveling mortar is in direct contact with the air, and the surface is directly subjected to the impact and wear of ground traffic. The thickness of the surface self-leveling mortar is relatively thin. When the ground base is solid, the bearing force is mainly concentrated on the surface. The surface damage of many floor materials is not due to insufficient compressive strength, but insufficient surface flexibility and wear resistance. Soon after opening and using, it shows peeling, sanding, pockmarking and cracking. Therefore, improving crack resistance, wear resistance and impact resistance is the technical difficulty of the research and development of surface self-leveling mortar.
[0005] The current prior art, such as CN201810979560.4, discloses a new type of highly efficient, environmentally friendly, water-resistant surface plaster gypsum mortar, including the following weight ratios: 700-800 parts of flue gas desulfurization gypsum, 100-200 parts of heavy calcium, 30-50 parts of kaolin, 30-50 parts of titanium dioxide, 1-2 parts of retarder, 25-35 parts of redispersible latex powder, 5-10 parts of cellulose ether, 1-3 parts of starch ether, 3-5 parts of water repellent, and 2-4 parts of polyacrylamide. Most of the prior art components are complex, and the raw materials are conventional raw materials. The comprehensive performance of the surface mortar is general, and it is difficult to have multiple properties such as crack resistance, wear resistance, and impact resistance. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a new type of surface mortar material, which has good mechanical properties and strong self-repairing function, and is suitable for use in various complex environments.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0008] A self-repairing surface mortar comprises the following raw materials: 180-230 parts of cement, 400-450 parts of aggregate, 80-110 parts of filler, 50-70 parts of redispersible latex powder, 30-50 parts of self-repairing silicon microspheres, 10-15 parts of polyvinyl alcohol fiber, 1-5 parts of defoaming agent, 0.5-1.5 parts of dispersant, 5-10 parts of composite expansion agent, 1-5 parts of water reducing agent, 1-3 parts of methyl hydroxypropyl cellulose ether and 80-100 parts of water.
[0009] Furthermore, the cement is ordinary Portland cement, grade 52.5R.
[0010] Furthermore, the aggregate is river sand that has been washed, dried and sieved and has a particle size of 2-4 mm.
[0011] Furthermore, the filler is obtained by mixing heavy calcium carbonate, fly ash and silica fume in a mass ratio of 1:1:1.
[0012] Furthermore, the redispersible latex powder is styrene acrylic latex powder or EVA latex powder.
[0013] Furthermore, the preparation method of the self-repairing silicon microspheres is:
[0014] (1) Dissolve 10 g of sucrose in 40 mL of deionized water, stir for 30 min, transfer into a 50 mL hydrothermal reactor, react at 200 °C for 4 h, and then cool to room temperature to obtain a brown colloidal solution product. Wash the product by centrifugation with deionized water and anhydrous ethanol for 3 times each, ultrasonically disperse it, dry it at 80 °C for 5 h, and grind it thoroughly to obtain carbon microspheres.
[0015] (2) 10 g of the carbon microspheres prepared in step (1) were placed in a container, 150 g of ethanol was added, and ultrasonic dispersion was performed for 30 minutes. Under magnetic stirring, 20 g of deionized water, 20 g of tetraethoxysilane TEOS and 8 mL of ammonia water were added respectively, and the mixture was reacted at room temperature for 24 hours. The mixture was filtered and washed three times with deionized water to obtain carbon microspheres of silicon dioxide.
[0016] (3) putting the carbon microspheres of silica into an alumina crucible and calcining them in a Ma furnace. During calcination, the heating rate was 1°C / min, and the temperature was kept at 500°C for about 2 hours, then the temperature was further increased to 610°C and kept for 10 hours, and then cooled to room temperature to obtain porous silica microspheres;
[0017] (4) At room temperature, the porous silica microspheres were added with sodium silicate solution and placed in a vacuum box for 12 h. The excess solution was filtered out and the microspheres were naturally dried. The solids were then immersed in a polyvinyl butyral solution dissolved in alcohol and heated. After sealing, the microspheres were placed in a water bath and heated at 65 °C for 3 h. After cooling, the self-healing silica microspheres were obtained.
[0018] Furthermore, in step (4), the solid-liquid ratio of the porous silica microspheres to the sodium silicate solution is 1 g:300 mL; the mass percentage concentration of the sodium silicate solution is 40-60%, and the mass ratio of alcohol to polyvinyl butyral in the polyvinyl butyral solution is 2:7; the particle size of the self-healing silicon microspheres obtained in step (4) is 50-100 nm, and the scanning electron microscope image of the obtained self-healing silicon microspheres is as follows: Figure 3 shown.
[0019] Furthermore, the defoaming agent is an organosilicon defoaming agent; the dispersing agent is xanthan gum, sodium fatty alcohol sulfate and sorbitol, with a mass ratio of (0.1-0.5):(3-5):(1-3); and the water reducer is a polycarboxylic acid water reducer.
[0020] Furthermore, the composite expansion agent is obtained by mixing calcium sulfoaluminate: calcium oxide: calcium sulfate in a mass ratio of 1:1:1.
[0021] A method for preparing a self-repairing surface mortar comprises the following preparation steps:
[0022] (1) Preparation of self-healing silicon microspheres;
[0023] (2) Place cement in a mixing container, add aggregate, filler, redispersible latex powder, self-healing silica microspheres, composite expansion agent and polyvinyl alcohol fiber in sequence, stir evenly, then add water, defoamer, dispersant, water reducer and methyl hydroxypropyl cellulose ether, and continue stirring for 15-20 minutes until mortar is formed.
[0024] Beneficial effects:
[0025] (1) The present invention scientifically selects various raw materials to prepare surface mortar. Using silicate cement as the surface mortar can not only provide high strength and good durability, but also has excellent frost resistance and protective effects, and is suitable for a variety of environments and engineering needs.
[0026] (2) Adding heavy calcium carbonate, fly ash and silica fume to form fillers. The fillers with pozzolanic activity will react with calcium hydroxide in the cement hydration products to form CSH gel, which can improve the density and mechanical properties of the material structure.
[0027] (3) Add dispersible latex powder. After the dispersible latex powder is added to cement, it forms an emulsion when it meets water and is evenly distributed in the cement paste. The polymer dispersion forms a film on the surface of the hydrate, and finally forms a continuous polymer network structure. The hydrate and the film cross-link and penetrate each other, improving the structural morphology inside the paste. When the cement body is subjected to stress, the polymer network can effectively absorb and transfer energy, thereby inhibiting the formation and expansion of cracks.
[0028] (4) Add defoamers, dispersants, water reducers, methyl hydroxypropyl cellulose ether and other ingredients. Defoamers can release bubbles entrained or generated in the mixture during the mixing process and construction process, improve compressive strength and improve surface conditions. Water reducers can improve the fluidity of cement mortar under low water-cement ratio conditions, reduce the amount of mixing water without reducing fluidity, improve the density of cement hardening structure, and improve mechanical properties. The use of dispersants can promote the uniform dispersion of fibers and various inorganic fillers. The use of methyl hydroxypropyl cellulose ether can enhance the bonding strength between mortar and base materials, make the mortar more bonded to the masonry surface, and thus improve the overall adhesion.
[0029] (5) The present invention prepares and adds a silicon microsphere with self-repairing function. The present invention uses silicon dioxide as the wall material, sodium silicate solution as the main capsule core material, and the outer layer is wrapped with a polyvinyl butyral coating. When cracks appear in the cement-based hardened matrix, external moisture and CO2 invade and form an alkaline environment at the cracks, causing the polyvinyl butyral coating film to gradually dissolve, and the porous silicon dioxide gradually releases the repair components, continuously filling and repairing the cracks and other damaged parts, and is well bonded with the surrounding hardened slurry, achieving the effect of repair and reinforcement.
[0030] (6) The present invention uses calcium sulfoaluminate, calcium oxide, and calcium sulfate to form a composite expansion agent. When calcium oxide is present, the hydration reaction of calcium sulfoaluminate can generate "colloidal" ettringite, which is helpful for the plugging and self-healing of cracks; the presence of calcium oxide can accelerate the hydration reaction of calcium sulfoaluminate to generate more ettringite, further promoting the repair of cracks; calcium sulfate can promote secondary hydration and carbonization, and these chemical reactions are helpful for the self-healing of cracks. The three work together to achieve the plugging and self-healing of cracks.
[0031] (7) In summary, the surface mortar of the present invention has fast early strength development, high later strength, excellent mechanical properties, good wear resistance and strong impact resistance, and is suitable for use in various scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The photos of crack changes of the specimens in Example 1 of the present invention at different days;
[0033] Figure 2The photographs of crack changes of the test pieces of Example 1 and Comparative Examples 1-7 of the present invention are shown;
[0034] Figure 3 This is a scanning electron microscope image of the self-healing silicon microspheres of Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0036] Example 1
[0037] A self-repairing surface mortar comprises the following raw materials: 180 parts of cement, 450 parts of aggregate, 110 parts of filler, 70 parts of redispersible latex powder, 30 parts of self-repairing silicon microspheres, 10 parts of polyvinyl alcohol fiber, 1 part of defoamer, 0.5 parts of dispersant, 5 parts of composite expansion agent, 1 part of water reducer, 1 part of methyl hydroxypropyl cellulose ether and 80 parts of water.
[0038] The cement is ordinary Portland cement, with the designation 52.5R.
[0039] The aggregate is river sand that has been washed, dried and sieved and has a particle size of 2-4 mm.
[0040] The filler is obtained by mixing heavy calcium carbonate, fly ash and silica fume in a mass ratio of 1:1:1.
[0041] The redispersible latex powder is styrene acrylic latex powder.
[0042] The preparation method of the self-repairing silicon microspheres is:
[0043] (1) Dissolve 10 g of sucrose in 40 mL of deionized water, stir for 30 min, transfer into a 50 mL hydrothermal reactor, react at 200 °C for 4 h, and then cool to room temperature to obtain a brown colloidal solution product. Wash the product by centrifugation with deionized water and anhydrous ethanol for 3 times each, ultrasonically disperse it, dry it at 80 °C for 5 h, and grind it thoroughly to obtain carbon microspheres.
[0044] (2) 10 g of the carbon microspheres prepared in step (1) were placed in a container, 150 g of ethanol was added, and ultrasonic dispersion was performed for 30 minutes. Under magnetic stirring, 20 g of deionized water, 20 g of TEOS and 8 mL of ammonia water were added respectively, and the mixture was reacted at room temperature for 24 hours. The mixture was filtered and washed three times with deionized water to obtain carbon microspheres of silicon dioxide.
[0045] (3) putting the carbon microspheres of silica into an alumina crucible and calcining them in a Ma furnace. During calcination, the heating rate was 1°C / min, and the temperature was kept at 500°C for about 2 hours, then the temperature was further increased to 610°C and kept for 10 hours, and then cooled to room temperature to obtain porous silica microspheres;
[0046] (4) At room temperature, the porous silica microspheres were added with sodium silicate solution and placed in a vacuum box for 12 h. The excess solution was filtered out and the microspheres were naturally dried. The solids were then immersed in a polyvinyl butyral solution dissolved in alcohol and heated. After sealing, the microspheres were placed in a water bath and heated at 65 °C for 3 h. After cooling, the self-healing silica microspheres were obtained.
[0047] In step (4), the solid-liquid ratio of the porous silica microspheres and the sodium silicate solution is 1 g:300 mL; the mass percentage concentration of the sodium silicate solution is 40%, and the mass ratio of alcohol to polyvinyl butyral in the polyvinyl butyral solution is 2:7.
[0048] The particle size of the self-repairing silicon microspheres obtained in step (4) is 50-100 nm.
[0049] The defoaming agent is an organosilicon defoaming agent; the dispersing agent is xanthan gum, sodium fatty alcohol sulfate and sorbitol, with a mass ratio of 0.1:3:3; and the water reducing agent is a polycarboxylic acid water reducing agent.
[0050] The composite expansion agent is obtained by mixing calcium sulfoaluminate: calcium oxide: calcium sulfate in a mass ratio of 1:1:1.
[0051] A method for preparing a self-repairing surface mortar comprises the following preparation steps:
[0052] (1) Preparation of self-healing silicon microspheres;
[0053] (2) Place cement in a mixing container, add aggregate, filler, redispersible latex powder, self-healing silica microspheres, composite expansion agent and polyvinyl alcohol fiber in sequence, stir evenly, then add water, defoamer, dispersant, water reducer and methyl hydroxypropyl cellulose ether, and continue stirring for 15 minutes until mortar is formed.
[0054] Example 2
[0055] A self-repairing surface mortar comprises the following raw materials: 200 parts of cement, 430 parts of aggregate, 95 parts of filler, 60 parts of redispersible latex powder, 40 parts of self-repairing silicon microspheres, 13 parts of polyvinyl alcohol fiber, 3 parts of defoamer, 1 part of dispersant, 6 parts of composite expansion agent, 5 parts of water reducer, 3 parts of methyl hydroxypropyl cellulose ether and 90 parts of water.
[0056] The cement is ordinary Portland cement, with the designation 52.5R.
[0057] The aggregate is river sand that has been washed, dried and sieved and has a particle size of 2-4 mm.
[0058] The filler is obtained by mixing heavy calcium carbonate, fly ash and silica fume in a mass ratio of 1:1:1.
[0059] The redispersible latex powder is EVA latex powder.
[0060] The preparation method of the self-repairing silicon microspheres is:
[0061] (1) Dissolve 10 g of sucrose in 40 mL of deionized water, stir for 30 min, transfer into a 50 mL hydrothermal reactor, react at 200 °C for 4 h, and then cool to room temperature to obtain a brown colloidal solution product. Wash the product by centrifugation with deionized water and anhydrous ethanol for 3 times each, ultrasonically disperse it, dry it at 80 °C for 5 h, and grind it thoroughly to obtain carbon microspheres.
[0062] (2) 10 g of the carbon microspheres prepared in step (1) were placed in a container, 150 g of ethanol was added, and ultrasonic dispersion was performed for 30 minutes. Under magnetic stirring, 20 g of deionized water, 20 g of TEOS and 8 mL of ammonia water were added respectively, and the mixture was reacted at room temperature for 24 hours. The mixture was filtered and washed three times with deionized water to obtain carbon microspheres of silicon dioxide.
[0063] (3) putting the carbon microspheres of silica into an alumina crucible and calcining them in a Ma furnace. During calcination, the heating rate was 1°C / min, and the temperature was kept at 500°C for about 2 hours, then the temperature was further increased to 610°C and kept for 10 hours, and then cooled to room temperature to obtain porous silica microspheres;
[0064] (4) At room temperature, the porous silica microspheres were added with sodium silicate solution and placed in a vacuum box for 12 h. The excess solution was filtered out and the microspheres were naturally dried. The solids were then immersed in a polyvinyl butyral solution dissolved in alcohol and heated. After sealing, the microspheres were placed in a water bath and heated at 65 °C for 3 h. After cooling, the self-healing silica microspheres were obtained.
[0065] In step (4), the solid-liquid ratio of the porous silica microspheres and the sodium silicate solution is 1 g:300 mL; the mass percentage concentration of the sodium silicate solution is 50%, and the mass ratio of alcohol to polyvinyl butyral in the polyvinyl butyral solution is 2:7.
[0066] The particle size of the self-repairing silicon microspheres obtained in step (4) is 50-100 nm.
[0067] The defoaming agent is an organosilicon defoaming agent; the dispersing agent is xanthan gum, sodium fatty alcohol sulfate and sorbitol, with a mass ratio of 0.3:4:1; and the water reducing agent is a polycarboxylic acid water reducing agent.
[0068] The composite expansion agent is obtained by mixing calcium sulfoaluminate: calcium oxide: calcium sulfate in a mass ratio of 1:1:1.
[0069] A method for preparing a self-repairing surface mortar comprises the following preparation steps:
[0070] (1) Preparation of self-healing silicon microspheres;
[0071] (2) Place cement in a mixing container, add aggregate, filler, redispersible latex powder, self-healing silica microspheres, composite expansion agent and polyvinyl alcohol fiber in sequence, stir evenly, then add water, defoamer, dispersant, water reducer and methyl hydroxypropyl cellulose ether, and continue stirring for 15 minutes until mortar is formed.
[0072] Example 3
[0073] A self-repairing surface mortar comprises the following raw materials: 230 parts of cement, 400 parts of aggregate, 80 parts of filler, 50 parts of redispersible latex powder, 50 parts of self-repairing silicon microspheres, 15 parts of polyvinyl alcohol fiber, 5 parts of defoamer, 1.5 parts of dispersant, 10 parts of composite expansion agent, 5 parts of water reducer, 3 parts of methyl hydroxypropyl cellulose ether and 100 parts of water.
[0074] The cement is ordinary Portland cement, with the designation 52.5R.
[0075] The aggregate is river sand that has been washed, dried and sieved and has a particle size of 2-4 mm.
[0076] The filler is obtained by mixing heavy calcium carbonate, fly ash and silica fume in a mass ratio of 1:1:1.
[0077] The redispersible latex powder is styrene acrylic latex powder.
[0078] The preparation method of the self-repairing silicon microspheres is:
[0079] (1) Dissolve 10 g of sucrose in 40 mL of deionized water, stir for 30 min, transfer into a 50 mL hydrothermal reactor, react at 200 °C for 4 h, and then cool to room temperature to obtain a brown colloidal solution product. Wash the product by centrifugation with deionized water and anhydrous ethanol for 3 times each, ultrasonically disperse it, dry it at 80 °C for 5 h, and grind it thoroughly to obtain carbon microspheres.
[0080] (2) 10 g of the carbon microspheres prepared in step (1) were placed in a container, 150 g of ethanol was added, and ultrasonic dispersion was performed for 30 minutes. Under magnetic stirring, 20 g of deionized water, 20 g of TEOS and 8 mL of ammonia water were added respectively, and the mixture was reacted at room temperature for 24 hours. The mixture was filtered and washed three times with deionized water to obtain carbon microspheres of silicon dioxide.
[0081] (3) putting the carbon microspheres of silica into an alumina crucible and calcining them in a Ma furnace. During calcination, the heating rate was 1°C / min, and the temperature was kept at 500°C for about 2 hours, then the temperature was further increased to 610°C and kept for 10 hours, and then cooled to room temperature to obtain porous silica microspheres;
[0082] (4) At room temperature, the porous silica microspheres were added with sodium silicate solution and placed in a vacuum box for 12 h. The excess solution was filtered out and the microspheres were naturally dried. The solids were then immersed in a polyvinyl butyral solution dissolved in alcohol and heated. After sealing, the microspheres were placed in a water bath and heated at 65 °C for 3 h. After cooling, the self-healing silica microspheres were obtained.
[0083] In step (4), the solid-liquid ratio of the porous silica microspheres and the sodium silicate solution is 1 g:300 mL; the mass percentage concentration of the sodium silicate solution is 60%, and the mass ratio of alcohol to polyvinyl butyral in the polyvinyl butyral solution is 2:7.
[0084] The particle size of the self-repairing silicon microspheres obtained in step (4) is 50-100 nm.
[0085] The defoaming agent is an organosilicon defoaming agent; the dispersing agent is xanthan gum, sodium fatty alcohol sulfate and sorbitol, with a mass ratio of 0.5:5:2; and the water reducing agent is a polycarboxylic acid water reducing agent.
[0086] The composite expansion agent is obtained by mixing calcium sulfoaluminate: calcium oxide: calcium sulfate in a mass ratio of 1:1:1.
[0087] A method for preparing a self-repairing surface mortar comprises the following preparation steps:
[0088] (1) Preparation of self-healing silicon microspheres;
[0089] (2) Place cement in a mixing container, add aggregate, filler, redispersible latex powder, self-healing silica microspheres, composite expansion agent and polyvinyl alcohol fiber in sequence, stir evenly, then add water, defoamer, dispersant, water reducer and methyl hydroxypropyl cellulose ether, and continue stirring for 15-20 minutes until mortar is formed.
[0090] Comparative Example 1
[0091] A self-repairing surface mortar comprises the following raw materials: 180 parts of cement, 450 parts of aggregate, 110 parts of filler, 70 parts of redispersible latex powder, 30 parts of silicon dioxide (particle size 50-100 nm), 10 parts of polyvinyl alcohol fiber, 1 part of defoamer, 0.5 parts of dispersant, 5 parts of composite expansion agent, 1 part of water reducing agent, 1 part of methyl hydroxypropyl cellulose ether, and 80 parts of water.
[0092] In this comparative example, except that an equal mass of silicon dioxide is used to replace the self-healing silicon microspheres, the other raw materials and preparation methods are the same as those of Example 1.
[0093] Comparative Example 2
[0094] A self-repairing surface mortar comprises the following raw materials: 180 parts of cement, 450 parts of aggregate, 110 parts of filler, 70 parts of redispersible latex powder, 30 parts of self-repairing silicon microspheres, 10 parts of polyvinyl alcohol fiber, 1 part of defoamer, 0.5 parts of dispersant, 5 parts of expansion agent, 1 part of water reducer, 1 part of methyl hydroxypropyl cellulose ether and 80 parts of water.
[0095] The expansion agent is calcium sulphoaluminate.
[0096] In this comparative example, except that only calcium sulfoaluminate is used as the expansion agent, the other raw materials and preparation method are the same as those in Example 1.
[0097] Comparative Example 3
[0098] A self-repairing surface mortar comprises the following raw materials: 180 parts of cement, 450 parts of aggregate, 110 parts of filler, 70 parts of redispersible latex powder, 30 parts of self-repairing silicon microspheres, 10 parts of polyvinyl alcohol fiber, 1 part of defoamer, 0.5 parts of dispersant, 5 parts of expansion agent, 1 part of water reducer, 1 part of methyl hydroxypropyl cellulose ether and 80 parts of water.
[0099] The expansion agent is calcium oxide.
[0100] In this comparative example, except that calcium oxide is used as the expansion agent, the other raw materials and preparation method are the same as those in Example 1.
[0101] Comparative Example 4
[0102] A self-repairing surface mortar comprises the following raw materials: 180 parts of cement, 450 parts of aggregate, 110 parts of filler, 70 parts of redispersible latex powder, 30 parts of self-repairing silicon microspheres, 10 parts of polyvinyl alcohol fiber, 1 part of defoamer, 0.5 parts of dispersant, 5 parts of expansion agent, 1 part of water reducer, 1 part of methyl hydroxypropyl cellulose ether and 80 parts of water.
[0103] The expansion agent is calcium sulfate.
[0104] In this comparative example, except that calcium sulfate is used as the expansion agent, the other raw materials and preparation method are the same as those in Example 1.
[0105] Comparative Example 5
[0106] A self-repairing surface mortar comprises the following raw materials: 180 parts of cement, 450 parts of aggregate, 110 parts of filler, 70 parts of redispersible latex powder, 30 parts of self-repairing silicon microspheres, 10 parts of polyvinyl alcohol fiber, 1 part of defoamer, 0.5 parts of dispersant, 5 parts of composite expansion agent, 1 part of water reducer, 1 part of methyl hydroxypropyl cellulose ether and 80 parts of water.
[0107] The composite expansion agent is obtained by mixing calcium sulphoaluminate and calcium oxide in a mass ratio of 1:1.
[0108] In this comparative example, except that only calcium sulfoaluminate and calcium oxide are used as the expansion agents, the other raw materials and preparation methods are the same as those in Example 1.
[0109] Comparative Example 6
[0110] A self-repairing surface mortar comprises the following raw materials: 180 parts of cement, 450 parts of aggregate, 110 parts of filler, 70 parts of redispersible latex powder, 30 parts of self-repairing silicon microspheres, 10 parts of polyvinyl alcohol fiber, 1 part of defoamer, 0.5 parts of dispersant, 5 parts of composite expansion agent, 1 part of water reducer, 1 part of methyl hydroxypropyl cellulose ether and 80 parts of water.
[0111] The composite expansion agent is obtained by mixing calcium sulfoaluminate and calcium sulfate in a mass ratio of 1:1.
[0112] In this comparative example, except that only calcium sulfoaluminate and calcium sulfate are used as the expansion agents, the other raw materials and preparation methods are the same as those in Example 1.
[0113] Comparative Example 7
[0114] A self-repairing surface mortar comprises the following raw materials: 180 parts of cement, 450 parts of aggregate, 110 parts of filler, 70 parts of redispersible latex powder, 30 parts of self-repairing silicon microspheres, 10 parts of polyvinyl alcohol fiber, 1 part of defoamer, 0.5 parts of dispersant, 5 parts of composite expansion agent, 1 part of water reducer, 1 part of methyl hydroxypropyl cellulose ether and 80 parts of water.
[0115] The composite expansion agent is obtained by mixing calcium oxide and calcium sulfate in a mass ratio of 1:1.
[0116] In this comparative example, except that only calcium oxide and calcium sulfate are used as the expander, the other raw materials and preparation method are the same as those in Example 1.
[0117] Performance Testing
[0118] The performance of the surface mortars prepared in Examples 1-3 and Comparative Examples 1-7 was compared, and the test method was referred to JC / T985-2017 "Cement-based self-leveling mortar for floor", as shown in Table 1:
[0119] Table 1 Test results of surface mortar performance
[0120]
[0121]
[0122] Self-healing capability test
[0123] Controlled crack specimen preparation:
[0124] The surface mortar prepared in Examples 1-3 and Comparative Examples 1-7 refers to the "Test Method for Cement Mortar Strength" (GB / T17671-2021), and the size of the cement mortar specimen is 40mm×40mm×160mm. After the specimen was cured in the curing room environment for 7 days, the DYF-300 cement pressure testing machine produced by Nanjing Yuda Xingke Instrument Technology Co., Ltd. was used to load the specimen to produce prefabricated cracks. First, place the cured specimen on the pressure testing machine, and then turn on the pressure testing machine to load the specimen. The specimen needs to be monitored during loading. When cracks appear, stop loading immediately, remove the specimen from the pressure testing machine, and measure the initial width d0 of the specimen crack.
[0125] Then all the specimens were placed in an outdoor curing environment and cured for 7d, 14d and 28d respectively, and then observed and measured again at the same position, and the final results were analyzed.
[0126] When testing the crack width change, the formula is used to calculate the crack closure rate. The formula is as follows:
[0127] Where Ψ is the crack closure rate, d0 is the initial width of the crack in the specimen (μm), and d t is the width of the crack in the specimen after curing for t days (μm).
[0128] Each group of experiments was repeated 5 times and the results were averaged.
[0129] Table 2 Crack closure rate
[0130]
[0131] From the data in Table 1-2, we can see that the test specimens of the embodiment of the present invention have good mechanical properties and excellent crack repair performance. However, in the comparative examples 1-7, which have changed the original composition, there is no addition of self-repairing silicon microspheres, and in the comparative examples 2-7, which have changed the composition of the expansion agent, the synergistic balance between the raw materials is broken, resulting in a decrease in the final comprehensive performance of the test specimens. The selection of raw materials in the present invention is critical to the mechanical properties and crack repair ability of the facing mortar. If one is missing, the effect will be weak.
[0132] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A self-repairing surface mortar, characterized in that: The invention comprises the following raw materials: 180-230 parts of cement, 400-450 parts of aggregate, 80-110 parts of filler, 50-70 parts of redispersible latex powder, 30-50 parts of self-healing silicon microspheres, 10-15 parts of polyvinyl alcohol fiber, 1-5 parts of defoaming agent, 0.5-1.5 parts of dispersant, 5-10 parts of composite expansion agent, 1-5 parts of water reducing agent, 1-3 parts of methyl hydroxypropyl cellulose ether and 80-100 parts of water.
2. The self-repairing surface mortar according to claim 1, characterized in that: The cement is ordinary Portland cement, with the designation 52.5R.
3. The self-repairing surface mortar according to claim 1, characterized in that: The aggregate is river sand that has been washed, dried and sieved and has a particle size of 2-4 mm.
4. The self-repairing surface mortar according to claim 1, characterized in that: The filler is obtained by mixing heavy calcium carbonate, fly ash and silica fume in a mass ratio of 1:1:
1.
5. The self-repairing surface mortar according to claim 1, characterized in that: The redispersible latex powder is styrene acrylic latex powder or EVA latex powder.
6. The self-repairing surface mortar according to claim 1, characterized in that: The preparation method of the self-repairing silicon microspheres is: (1) Dissolve 10 g of sucrose in 40 mL of deionized water, stir for 30 min, transfer into a 50 mL hydrothermal reactor, react at 200 °C for 4 h, and then cool to room temperature to obtain a brown colloidal solution product. Wash the product by centrifugation with deionized water and anhydrous ethanol for 3 times each, ultrasonically disperse it, dry it at 80 °C for 5 h, and grind it thoroughly to obtain carbon microspheres. (2) 10 g of the carbon microspheres prepared in step (1) were placed in a container, 150 g of ethanol was added, and ultrasonic dispersion was performed for 30 minutes. Under magnetic stirring, 20 g of deionized water, 20 g of TEOS and 8 mL of ammonia water were added respectively, and the mixture was reacted at room temperature for 24 hours. The mixture was filtered and washed three times with deionized water to obtain carbon microspheres of silicon dioxide. (3) putting the carbon microspheres of silica into an alumina crucible and calcining them in a Ma furnace. During calcination, the heating rate was 1°C / min, and the temperature was kept at 500°C for about 2 hours, then the temperature was further increased to 610°C and kept for 10 hours, and then cooled to room temperature to obtain porous silica microspheres; (4) At room temperature, the porous silica microspheres were added with sodium silicate solution and placed in a vacuum box for 12 h. The excess solution was filtered out and the microspheres were naturally dried. The solids were then immersed in a polyvinyl butyral solution dissolved in alcohol and heated. After sealing, the microspheres were placed in a water bath and heated at 65 °C for 3 h. After cooling, the self-healing silica microspheres were obtained.
7. The self-repairing surface mortar according to claim 6, characterized in that: In step (4), the solid-liquid ratio of the porous silica microspheres and the sodium silicate solution is 1 g:300 mL; the mass percentage concentration of the sodium silicate solution is 40-60%, and the mass ratio of alcohol to polyvinyl butyral in the polyvinyl butyral solution is 2:
7.
8. The self-repairing surface mortar according to claim 1, characterized in that: The defoaming agent is an organosilicon defoaming agent; the dispersing agent is xanthan gum, sodium fatty alcohol sulfate and sorbitol, with a mass ratio of (0.1-0.5): (3-5): (1-3); and the water reducing agent is a polycarboxylic acid water reducing agent.
9. The self-repairing surface mortar according to claim 1, characterized in that: The composite expansion agent is obtained by mixing calcium sulfoaluminate: calcium oxide: calcium sulfate in a mass ratio of 1:1:
1.
10. A method for preparing the self-repairing surface mortar according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: (1) Preparation of self-healing silicon microspheres; (2) Place cement in a mixing container, add aggregate, filler, redispersible latex powder, self-healing silica microspheres, composite expansion agent and polyvinyl alcohol fiber in sequence, stir evenly, then add water, defoamer, dispersant, water reducer and methyl hydroxypropyl cellulose ether, and continue stirring for 15-20 minutes until mortar is formed.
Citation Information
Patent Citations
Novel high-efficiency environment-friendly waterproof surface plastering gypsum mortar
CN108751903A